Species Differences in Ezetimibe Glucuronidation - Shalom Emmanuel; Eric A. Asare; Ting Du; Huan Xie; Dong Liang; Song Gao (Metabolites)
Background: Peclinical and clinical studies have revealed that ezetimibe, an approved cholesterol-absorption inhibitor, is rapidly and extensively metabolized to a more potent metabolite, ezetimibe glucuronide. Since different species are commonly used in the pharmacokinetic and pharmacodynamic studies of ezetimibe, it is essential to determine the species difference in glucuronidation of ezetimibe in order to accurately evaluate ezetimibe’s pharmacokinetics and pharmacodynamics. The purpose of the study was to compare species differences in ezetimibe glucuronidation rates using intestinal microsomes from humans, rats, mice, monkeys, and dogs. Method: Intestinal microsomes from different species were used to assess the ezetimibe glucuronidation rates. Multiple substrate concentrations at 0.5, 2, 5, 10, 20, 30, 40, and 50 µM were tested and fitted into the Michaelis–Menten model to determine the enzyme kinetic parameters. Results: The results showed that the glucuronidation rates with these tested species were significantly different. Kinetic studies revealed that the maximum metabolic rate (Vmax) was higher in monkeys (3.87 ± 0.22 nmol/mg/min) than that in rat (2.40 ± 0.148 nmol/mg/min) and mouse (2.23 ± 0.10 nmol/mg/min), and then human (1.90 ± 0.08 nmol/mg/min) and dog (1.19 ± 0.06 nmol/mg/min). The CLint was an 8.17-fold difference among these species, following the order of mouse > dog > human > rat = monkey. Conclusions: The study revealed that the rate of ezetimibe glucuronidation in the intestine was different in different species and has an impact on ezetimibe glucuronidation in the intestine. When analyzing the pharmacodynamics, pharmacokinetics, or toxicology of ezetimibe using different models, these species differences must be taken into consideration.